Translasi dan validasi iowa infant feeding attitude scale di indonesia - Fitria Siswi Utami (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
The existence of an instrument to measure mothers’ perception on exclusive breastfeeding and infant feeding nutrition is needed. The purpose of this study is to determine the validity and reliability of Iowa Infant Feeding Attitude Scale (IIFAS) in Indonesia community. This study is an pilot study for the next research. The result shows that the feeding attitude scale has validity with Cronbach alpha was 0.87. Item number 17 was deleted. These results indicate that the instrument has validity and reliability to implement among breastfeeding mothers in Indonesia in order to determine their perception on breastfeeding.